Amici come prima? Italy and Germany in times of crisis. Issue 1 (2nd January 2018) - Piattoni, Simona; Verzichelli, Luca; Wagemann, Claudius
ABSTRACT: This introduction justifies the decision to focus on Italo-German relations – and in particular on the way in which prejudices and stereotypes affect them – in light of a long history of parallel political and economic development of the two countries and the central role that they are likely to play in the next phase of European integration. After briefly presenting the chapters that compose the special issue, the introduction dwells on the importance of analysing both bilateral and transnational relations at EU level as they reciprocally influence the role that these two major EU member states may play in Europe.